The Effect of Educational Monopoly Learning Media on Fourth-Grade Students' Achievement in Fraction Operations - Yurika Gustiyani Rasyidina; Kowiyah Kowiyah (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
Underperformance in mastering fraction operations continues to pose a significant obstacle within elementary mathematics instruction, largely attributable to traditional teaching approaches and insufficient integration of interactive educational resources. The present investigation sought to assess the impact of an Educational Monopoly (Monopoly Edukatif) instructional tool on the academic performance of fourth-grade learners in fraction operations at SDN Jatibening 04. The study adopted a quantitative framework utilizing a quasi-experimental design with a Posttest-Only Control Group configuration. A total of 60 fourth-grade students were recruited through purposive sampling techniques, equally distributed into an experimental cohort and a control cohort of 30 students each. Students in the experimental condition engaged with instruction facilitated by the Educational Monopoly tool, while those in the control condition experienced traditional pedagogical methods. Performance data were gathered via a posttest comprising five open-ended questions and subjected to descriptive statistical procedures, Shapiro–Wilk normality assessment, Levene's homogeneity verification, independent-samples t-test, and Cohen's d for effect magnitude estimation. Findings demonstrated a statistically significant disparity in academic performance between the cohorts (t = 6.745, p < 0.001). Students in the experimental condition attained a superior mean posttest score (M = 78.33) compared to their counterparts in the control condition (M = 62.00). Additionally, the computed effect magnitude (Cohen's d = 1.74) reflected a substantial practical significance. These outcomes indicate that the Educational Monopoly instructional tool serves as an efficacious pedagogical resource for enhancing elementary students' competency in fraction operations through fostering active engagement, facilitating deeper conceptual understanding, and increasing overall classroom involvement.